2013
DOI: 10.1095/biolreprod.112.103374
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin O Regulates Germinal Vesicle Breakdown in Mouse Oocytes1

Abstract: It is well accepted that oocyte meiotic resumption is mainly regulated by the maturation-promoting factor (MPF), which is composed of cyclin B1 (CCNB1) and cyclin-dependent kinase 1 (CDC2). Maturation-promoting factor activity is regulated by the expression level of CCNB1, phosphorylation of CDC2, and their germinal vesicle (GV) localization. In addition to CCNB1, cyclin O (CCNO) is highly expressed in oocytes, but its biological functions are still not clear. By employing short interfering RNA microinjection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…elegans , CKSs were demonstrated to have an essential role in meiosis M phase exit [ 92 ]; mice lacking CKS2, a mammalian homolog of yeast CKS1, were viable but sterile due to failure of female germ cells to progress past the first meiotic metaphase [ 93 ]. Likewise, CCNO is a cyclin acting as upstream regulator of MPF and demonstrated to play an important role in mouse oocytes since the CCNO knockdown blocked meiosis resumption [ 94 ]. Thus, higher expression of transcripts encoding CKS1 and CCNO in REL oocytes, might suggest that higher synthesis of cell-cycle regulators is necessary for scallop oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…elegans , CKSs were demonstrated to have an essential role in meiosis M phase exit [ 92 ]; mice lacking CKS2, a mammalian homolog of yeast CKS1, were viable but sterile due to failure of female germ cells to progress past the first meiotic metaphase [ 93 ]. Likewise, CCNO is a cyclin acting as upstream regulator of MPF and demonstrated to play an important role in mouse oocytes since the CCNO knockdown blocked meiosis resumption [ 94 ]. Thus, higher expression of transcripts encoding CKS1 and CCNO in REL oocytes, might suggest that higher synthesis of cell-cycle regulators is necessary for scallop oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream from the MCIDAS/E2F complex also lies CCNO ( Fig. 1) (Stubbs et al 2012;Ma et al 2014;Wallmeier et al 2014), a cyclin-like protein first shown to be involved in oocyte meiosis resumption and apoptosis (Roig et al 2009;Ma et al 2013), and then shown to be expressed in MCC progenitors in the Xenopus skin and in the mouse brain, airways, and oviducts (Stubbs et al 2012;Funk et al 2015;Amirav et al 2016). Although its partners and molecular function remain to be determined, CCNO mutations or depletion lead to defects comparable to the C-MYB phenotype: defects in BB amplification, docking, and ciliogenesis Funk et al 2015).…”
Section: Downstream Effectors Of the MCC Differentiation Programmentioning
confidence: 99%
“…Cyclin B3 is a newly discovered cyclin that potentially forms active kinase complexes with CDK1; its knockdown and knockout arrested the oocytes at metaphase I [11–13]. Cyclin O (CCNO, also called UNG2 or UDG2) is a novel cyclin family protein expressed in oocytes whose knockdown inhibited CDK1 (Tyr15) dephosphorylation and arrested oocytes at the germinal vesicle (GV) stage [14]; however, Ccno -deficient male and female mice are partly fertile [15]. In this review, we will summarize and discuss the functions of various cyclins mentioned above in line with time course of meiotic maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin O is highly expressed in oocytes and localizes in the nucleus of GV-stage oocytes. We found that cyclin O was essential for oocyte meiotic resumption because Ccno knockdown inhibited CDK1 (Tyr15) dephosphorylation, which was required for MPF activation [14]. Ccno knockout mice have been generated, and 57% mutant mice developed a prominent hydrocephalus, leading to abnormal head morphology and growth retardation; remaining male and female mice that were not severely affected by hydrocephalus were fertile at maturity age [15].…”
Section: Introductionmentioning
confidence: 99%